Networked Embedded Computing:: Current Developments for Tomorrow’s Architecture - McCartney, Kevin (ARCC Conference Repository, 2019)
This paper reviews current ideas and technology related to the development of embedded computing systems in buildings. It concludes with a prioritization of systems to be selected for integration in a new research building to be constructed in 2008-09 in Cork Ireland.